2017
DOI: 10.1002/jrs.5202
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Raman microscopy to identify micro‐residues related to tool‐use and modern contaminants on prehistoric stone artefacts

Abstract: Analyses of ancient micro‐residues and usewear preserved on stone artefacts can potentially provide detailed information about how prehistoric humans used the artefacts to process materials such as food, pigments and/or adhesives. However, ancient micro‐residues are likely degraded, and there are multiple potential sources of contamination, such as contact with sediments, groundwater, recent handling, storage materials or laboratory conditions, any of which can inhibit reliable identification of micro‐residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…These characteristics are observed when the materials are fired. Comparison to the data obtained in the previous studies showed that the Raman spectroscopy confirmed that this spectrum was similar to that of the artificially produced [Ca 2 (PO 4 ) 2 ], bones containing collagen, and materials taken from burned animal bones(Figure 7)(Bordes et al, 2017;Marques et al, 2018;Jillavenkatesa and Condrate Sr, 1998).Natural white materials with Ca and P as the main elements, include fluorapatite[Ca 5 (PO 4 ) 3 F 2 ], which is a major component of teeth and bones. Fluorapatite mostly comes from Canada, Mexico, Brazil, Russia, Japan, and Myanmar, and is not produced in Korea(Doopedia, 2020).…”
supporting
confidence: 75%
“…These characteristics are observed when the materials are fired. Comparison to the data obtained in the previous studies showed that the Raman spectroscopy confirmed that this spectrum was similar to that of the artificially produced [Ca 2 (PO 4 ) 2 ], bones containing collagen, and materials taken from burned animal bones(Figure 7)(Bordes et al, 2017;Marques et al, 2018;Jillavenkatesa and Condrate Sr, 1998).Natural white materials with Ca and P as the main elements, include fluorapatite[Ca 5 (PO 4 ) 3 F 2 ], which is a major component of teeth and bones. Fluorapatite mostly comes from Canada, Mexico, Brazil, Russia, Japan, and Myanmar, and is not produced in Korea(Doopedia, 2020).…”
supporting
confidence: 75%
“…Moreover, a sharp band is observed at 1,052 cm −1 which can be attributed to calcium nitrate. As observed by Bordes and colleagues, the calcium nitrate could arise from a degradation process that occurred postdepositionally. It is not impossible that the bands at 1,003 and 1,052 cm −1 originated from burkeite.…”
Section: Resultsmentioning
confidence: 74%
“…Raman spectrometry was the most suitable technique considering is high spatial resolution and its non-invasive application. This technique is becoming increasingly common in analysis of residues on stone tools 21,22 and is used here to corroborate visual identification of plant residues.…”
Section: Resultsmentioning
confidence: 99%